Penamaan Jalan di Kecamatan Gisting: Kajian Lanskap Linguistik dan Onomastika - Argandari, Rozana (Research Community for Critical Society and Environment, 2025)
The surrounding public is influenced by the correlations and conventions of language, which can be studied as a linguistic landscape. This study aims to investigate the philosophical significance of street naming conventions in the Gisting District, exploring how linguistic landscapes reflect and influence public perception and social identity. The combination of these two studies requires analyzing data from 30 texts and visual sources, as well as 18 structures, forms, and meanings in morphemes. The method used is a qualitative descriptive approach, employing a portrait method with photographs and a word-reading technique. The results of the research reveal the meanings of words, both as lexemes and as compound words, which possess philosophical significance in the context of language activity and the philosophy of language. Eventually, understanding the onomastic choices can aid in preserving the district's history and promoting tourism by highlighting significant local figures or events associated with the street names.